The effectiveness and safety of neoadjuvant pertuzumab and trastuzumab in women with locally advanced, inflammatory, or early-stage human epidermal growth factor receptor 2-positive breast cancer: Turkish Oncology Group study. Issue 7 (20th June 2022) - Özdemir, Özlem; Zengel, Baha; Yildiz, Yaşar; Uluç, Basak Oyan; Cabuk, Devrim; Ozden, Ercan; Salim, Derya Kivrak; Paydas, Semra; Demir, Atakan; Diker, Omer; Pilanci, Kezban Nur; Sönmez, Özlem Uysal; et al.
Abstract : In our study, we aimed to evaluate the pathological response rates and side effect profile of adding pertuzumab to the treatment of HER2+ locally advanced, inflammatory, or early-stage breast cancer. This study was conducted by the Turkish Oncology Group (TOG) with data collected from 32 centers. Our study was multicentric, and a total of 364 patients were included. The median age of the patients was 49 years (18–85 years). Two hundred fifteen (60%) of the cases were hormone receptor/HER2+ positive(ER+ or PR+, or both), and 149 (40%) of them were HER2-rich (ER and PR negative). The number of complete responses was 124 (54%) in the docetaxel+trastuzumab+pertuzumab arm and 102 (45%) in the paclitaxel+trastuzumab+pertuzumab arm, and there was no difference between the groups in terms of complete response. In 226 (62%) patients with complete response, a significant correlation was found with DCIS, tumor focality, removed lymph node, and ER status P < 0.05. Anemia, nausea, vomiting, myalgia, alopecia, and mucosal inflammation were significantly higher in the docetaxel arm, P < 0.05. In our study, no statistical difference was found between the before–after echocardiography values. DCIS positivity in biopsy before neoadjuvant chemotherapy, tumor focality; the number of lymph nodes removed and ER status were found to be associated with pCR. In conclusion, we think that studies evaluating pCR-related clinicopathological variables and radiological imaging features will play a critical role in the development of nonsurgical treatment approaches.